The Welfare Use of Immigrants and Natives in Germany: The Case of Turkish Immigrants - Riphahn, Regina Therese; Wunder, Christoph; Sander, Monika (International Journal of Manpower, 2013)
This paper analyzes the welfare use of Turkish immigrants and natives in Germany. After a brief description of the system of minimum income protection and its recent reform we use data from the German Socio-Economic Panel Study to investigate the correlates of transfer receipt for the two subsamples. Immigrants of Turkish origin have a higher propensity to use welfare benefits than natives. After controlling for general individual and household level characteristics the difference in welfare receipt is statistically significant only for the group of second generation immigrants. The correlation of observable characteristics with welfare dependence differs significantly for the native and immigrant sampl
WiSo-Import:2015-03-26:932
Keywords: Unemployment benefits; Transformation; social assisstance; Immigration